Dire straits : the perils of writing the early modern English coastline from Leland to Milton - Bellamy, Elizabeth J. (Elizabeth Jane) (University of Toronto Press, 2013)
By illustrating how early modern English writers created their works in the context of a longstanding cultural inheritance from antiquity, Elizabeth Jane Bellamy offers a new approach to the history of early modern cartography and its influences on literature.
5 Coda : Exiting the Shadow of Ultima Britannia in Paradise Lost.
Keywords: English poetry -- Early modern, 1500-1700 -- History and criticism.; Coasts in literature.; Cartography in literature.; Landscapes in literature.; England -- In literature.; Littoral dans la littérature.; Cartographie dans la littérature.; Paysages dans la littérature.; Angleterre -- Dans la littérature.; LITERARY CRITICISM -- Medieval.; POETRY -- English, Irish, Scottish, Welsh.; Cartography in literature; Coasts in literature; English poetry -- Early modern; Landscapes in literature; Literature; England; Frühneuenglisch; Literatur; Küste -- Motiv; 1500-1700; Criticism, interpretation, etc.